Pengembangan Instrumen Pengukur Pengetahuan Sumber Daya Air Bagi Siswa SMA/MA - Linda Linda; Febrianawati Yusup (Universitas Veteran Bangun Nusantara Sukoharjo, 2020)
This study aims to develop valid research instruments and can be used to measure the knowledge of high school students as equals about water resources. The stages in the development of instruments carried out are the development of a collection of question items, validation of a collection of question items to school namely to biology teachers and to biology lecturers, taking expert opinions, testing validated instruments, administering instruments, and calculating instrument validity and reliability. This instrument contains statements to measure knowledge about water resources. The instrument validation phase was handed over to one biology teacher, and two biology education lecturers. The trial of this instrument was conducted on 26 high school students equivalent. The results of this trial show that out of the fifteen item items only six items are suitable that can be used to measure high school students' knowledge of water resources. The six question items consist of true and incorrect item items. Cronbach's alpha coefficient is -0.65. According to these findings, it can be concluded that the instrument is invalid and cannot be used to measure students' knowledge of water resources.Keywords: Instrument Development, Knowledge, Water Resources.